Optimalisasi Kinerja Alat Homogenizer Terhadap Peningkatan Pelayanan Pengujian Mutu Benih - Prayitno, Prayitno; Mukhlis, Syaiful; Hariyanto, Budi; Eka Putra, Herman Estu; Sofiana, Rina (Jurnal Pengelolaan Laboratorium, 2025)
This study aims to improve or optimize the performance of the homogenizer in homogenizing seed samples and facilitate its operational performance so that the results obtained are in accordance with the International Seed Testing Association (ISTA). The homogenizer uses a mechanical transmission that includes a belt transmission from the power source to the gearbox, while from the gearbox to the drum/container using a chain transmission that produces a more stable drum rotation and does not slip so that it can maximize the function of the homogenizer. The addition of inlet holes and exit holes facilitates the operation of the homogenizer. This tool modification increases ergonomic value and supports tool optimization. Good homogenizer conditions will provide maximum and good service in the seed quality testing stage, especially compositing/mixing seeds before analysis. So that it will support the smoothness and accuracy of testing and student practicum activities, teaching staff research, and external stakeholders.